Integrasi Manajemen dan Teknologi Informasi dalam Pelatihan Media Pembelajaran dan Branding Sekolah - Lale Puspita Kembang; Lalu Delsi Samsumar; Zaenudin Zaenudin; Amiruddin Kalbuadi; Dewi Rispawati (FKIP, Universitas Palangka Raya, 2026)
This community service program aims to enhance the competencies of teachers at MA Attarbiyah Addiniyah Gersik in utilizing information technology and strengthening school branding through an integrative approach combining Management and Information Technology. The one‑month program consisted of needs analysis, program design, pre‑test, basic computer training, digital learning media development, school branding training, mentoring, and post‑test evaluation. The pre‑test and post‑test results indicate significant improvements in all competency areas: basic computer skills (57.7%), digital learning media development (83.3%), and school branding (45.4%). Observations during the training revealed increased teacher confidence in using digital tools, improved ability to produce engaging learning media, and better understanding of school branding strategies. The mentoring phase supported teachers in completing their final outputs, including digital learning media and a school branding concept. Overall, this program contributed to improving teachers’ digital literacy, enhancing learning quality, strengthening teacher professionalism, and reinforcing the school’s digital identity.